2023
DOI: 10.3390/ani13071137
|View full text |Cite
|
Sign up to set email alerts
|

Black Soldier Fly Larva Fat in Broiler Chicken Diets Affects Breast Meat Quality

Abstract: This study aimed to evaluate the dose-dependent effect of black soldier fly (BFL) larvae fat inclusion in broiler chicken diets on breast meat quality. Four hundred 1-day-old male birds (Ross 308) were assigned to the following four treatments (10 replicates with 10 birds each): HI0, a basal diet without dietary fat inclusion, and HI03, HI06, and HI09, basal diets enriched with 30 g/kg, 60 g/kg, and 90 g/kg of BSF larvae fat, respectively. Principal component analysis showed noticeable differentiation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In addition, a* (redness) and b* (yellowness) values increased with dietary supplementation of BSFLO-Sca. In agreement with these findings, dietary BSFLO increased the L*, a*, and b* values of the breast meat broiler ( Schiavone et al, 2019 ; Kierończyk et al, 2023 ). Increased breast meat color results from an accumulation of xanthophyll pigments from BSF larvae.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, a* (redness) and b* (yellowness) values increased with dietary supplementation of BSFLO-Sca. In agreement with these findings, dietary BSFLO increased the L*, a*, and b* values of the breast meat broiler ( Schiavone et al, 2019 ; Kierończyk et al, 2023 ). Increased breast meat color results from an accumulation of xanthophyll pigments from BSF larvae.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, supplementation of BSFLO-SCa affected the FA profiles of broiler. The available literature observed the same in broiler ( Cullere et al, 2019 ; Kim et al, 2020 ; Kierończyk et al, 2023 ). BSFLO-SCa significantly increased MCFA (lauric and myristic) and MUFA in meat.…”
Section: Discussionmentioning
confidence: 53%
“…Research also points to the possibility of BSFL meal and fat completely replacing soybean cake and oil in diets for laying hens, indicating a substantial shift in traditional poultry feeding practices [71]. The impact of BSFL larva fat on broiler diets extends to the quality of the chicken meat itself, particularly affecting breast meat quality [72]. Furthermore, modified BSF larva fat in broiler diets has been examined for its effects on performance, carcass traits, blood parameters, histomorphological features, and gut microbiota, demonstrating its comprehensive impact on poultry health and product quality [73].…”
Section: Fat Bioavailabilitymentioning
confidence: 99%
“…Insect dietary fat is a byproduct of protein meal produced by various extraction methods, such as solvent systems, mechanical separation and/or pressing, Soxhlet extraction, and supercritical extraction (Kierończyk et al, 2022b). Overall, incorporating insect dietary fat into poultry diets, including those for broilers (Kierończyk et al, 2023), laying hens (Heuel et al, 2021), turkeys (Sypniewski et al, 2020), and pheasants (Flis et al, 2024), has been shown to yield positive results. Growth performance outcomes are comparable to those achieved with commonly used dietary fats, such as soybean oil, palm oil, or poultry fat (Schiavone et al, 2018;Benzertiha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have neither shown adverse effects on the weight or length of selected gastrointestinal tract (GIT) segments (Kierończyk et al, 2020) nor on favourable nutrient utilisation, particularly for the coefficients of ether extract ileal digestibility (Kierończyk et al, 2022c). The insect fatty acid (FA) profile, in terms of saturated fatty acid (SFA) and unsaturated fatty acid (UFA) levels, is defined between that of animal fats and oils of plant origin (Sosa and Fogliano, 2017;Kierończyk et al, 2023). However, the predominant FAs in Hermetia illucens (HI) larvae, a preferred species for insect production in mini-livestock farming, include lauric (C12:0), myristic (C14:0), palmitic (C16:0), palmitoleic (C16:1), oleic (C18:1), and linoleic (C18:2) acids (Kierończyk et al, 2022a) further implementation of meals and fats derived from invertebrates to livestock (poultry and swine).…”
Section: Introductionmentioning
confidence: 99%